Experimental investigation of seashell concrete with anti-corrosion agent enhancement - Abbas Ali; Abdalla Khalid; Saji Gopika (MATEC Web of Conferences)
This research investigates the performance of seashell concrete enhanced with anti-corrosion agents, focusing on sustainability and durability. The study evaluates workability, density, compressive strength, modulus of elasticity, and corrosion resistance. Results show that seashell powder improves workability and density but requires adjustments due to higher water absorption and lower specific gravity. The control mix (30% seashell powder) achieved 42 MPa compressive strength and 35 GPa modulus of elasticity. Adding 4% NitCal reduced these values to 38 MPa and 28 GPa, while 8% NitCal further decreased them to 30 MPa and 28 GPa. However, 8% NitCal significantly enhanced corrosion resistance, delaying crack formation from 72 hours to 220 hours and reducing corrosion current. Although anti-corrosion agents slightly increased the carbon footprint, seashell powder improved sustainability by reducing cement dependency. The findings highlight the potential of seashell concrete with anti-corrosion additives for durable, eco-friendly construction. Future research should optimize formulations and assess long-term performance to maximize benefits.